How Company Growth Moderates the Determinants of Firm Value: A Panel MRA Study of Indonesian Banks, 2020–2024 - Wardana, Atik Kusuma; Zulfiati, Lies (Santoso Academy Network, 2026)
This study examines the effects of managerial ownership, firm size, and dividend policy on firm value, with company growth as a moderating variable, using panel data from banking firms listed on the Indonesia Stock Exchange during 2020–2024. Adopting a quantitative approach, secondary data from annual reports are analyzed using fixed-effects panel regression and Moderated Regression Analysis (MRA). Firm value is measured using a market-based valuation proxy, while managerial ownership, firm size, dividend policy, and company growth reflect governance structure, organizational scale, financial policy, and growth dynamics. The results show that managerial ownership and firm size have a positive and significant impact on firm value, whereas dividend policy has no significant effect. Moderation analysis indicates that company growth strengthens the relationship between managerial ownership and firm value and moderates the effect of firm size on firm value, but does not moderate the relationship between dividend policy and firm value. These findings suggest that growth-oriented banks are more effective in translating ownership alignment and organizational scale into higher market valuation and highlight the importance of ownership alignment, scale optimization, and sustainable growth strategies over dividend signaling.